Combining magnetic resonance imaging within six‐hours of symptom onset with clinical follow‐up at 24 h improves prediction of 'malignant' middle cerebral artery infarction. Issue 2 (9th July 2013) - Kruetzelmann, Anna; Hartmann, Frank; Beck, Christoph; Juettler, Eric; Singer, Oliver C.; Köhrmann, Martin; Kersten, Jan F.; Sobesky, Jan; Gerloff, Christian; Villringer, Arno; Fiehler, Jens; Neumann‐Haefelin, Tobias; et al.
<x xml:space="preserve">Abstract</x> Background A large diffusion‐weighted imaging lesion ≤six‐hours of symptom onset was found to predict the development of 'malignant' middle cerebral artery infarction with high specificity, positive predictive value, and negative predictive value, but sensitivity was low. Hypothesis We tested the hypothesis that sensitivity can be improved by adding information from clinical follow‐up examination after 24 h. Methods We analyzed data from a prospective, multicenter, observational cohort study of patients with acute ischemic stroke and middle cerebral artery occlusion studied by stroke magnetic resonance imaging ≤six‐hours of symptom onset. We used the National Institutes of Health Stroke Scale to assess severity of symptoms after 24 h. We used the Classification and Regression Trees analysis to define the optimal thresholds of diffusion‐weighted imaging lesion volume and the National Institutes of Health Stroke Scale after 24 h in patients developing 'malignant' middle cerebral artery infarction. We calculated sensitivity, specificity, positive predictive value, and negative predictive value for two simple predictive models based on acute diffusion‐weighted imaging lesion volume alone and acute diffusion‐weighted imaging lesion volume together with the National Institutes of Health Stroke Scale after 24 h. Results Of 135 patients, 27 (20%) developed a 'malignant' middle cerebral artery infarction. The Classification and Regression Trees analysis identified acute diffusion‐weighted imaging lesion ≥78 ml and the National Institutes of Health Stroke Scale score after 24 h ≥22 as optimal cut‐offs. Inclusion of the National Institutes of Health Stroke Scale score after 24 h in a simple two‐step decision tree increased sensitivity from 0·59 to 0·79, while specificity, positive predictive value, and negative predictive value remained largely unchanged. Conclusion Clinical follow‐up examination after 24 h helps identify patients at risk of 'malignant' middle cerebral artery infarction that are missed by predictive algorithms based on early diffusion‐weighted imaging lesion volume alone.